Assessing Urban and Rural Teachers’ Competencies in STEM Integrated Education in Malaysia - Khairani, Ahmad Zamri (EDP Sciences, 2017)
In order to fulfil the need of sizeable skill workers, Malaysia will introduce STEM integration education in mainstream schools throughout the country. However, like any educational reform, one important issue that needs to be taken into account is the teachers’ readiness especially in terms of their skills and competency in implementing the reform. As such, the purpose of this study is to assess differences between teachers’ competency for STEM integration education between urban and rural teachers. A total of 244 teachers (urban = 129, rural = 115) are employed as sample in this cross-sectional quantitative study. Responses from an 18-item questionnaire were analysed using Rasch Model analysis to determine characteristics of item that measure competency between urban and rural teachers. The DIF analysis shows that items related to competency in (1) ICT integration, and (2) organizing co-curricular activities showed a significant difference in their measures between both sets of teachers. The result from this study would certainly provide useful information to relevant stakeholders, especially with regards to providing training for the teachers in the designated areas.